2012
DOI: 10.1182/blood.v120.21.711.711
|View full text |Cite
|
Sign up to set email alerts
|

SF3B1 Mutations in CLL Are Equivalent to p53/ATM Dysfunction and Cause Defective Puma Upregulation in Response to Chemotherapy

Abstract: 711 Mutations or deletions of the tumor suppressor p53 or its upstream kinase ATM are well-known determinants of poor prognosis in Chronic Lymphocytic Leukemia (CLL). In recent years, genome wide sequencing has uncovered novel gene mutations that correspond with poor prognosis. Specifically, recurrent mutations in the splicing factor SF3B1 and the Notch and NRAS/KRAS oncogenes have been found. These mutations were (in part) mutually exclusive with p53 and/or ATM mutations, which suggested overla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“… 26 An alternative assay, based on measuring CDKN1A levels by RT-PCR following fludarabine and doxorubicin treatment, was primarily designed for ATM function testing and can also distinguish between TP53 and ATM defects. 11 As we have previously published, also cell death following DNA-damaging agents can distinguish a group of functional WT samples from a group of ATM -mutated and a group of TP53 -mutated samples; 22 however, this method seems less suitable to functionally test samples at the individual level to predict (dys)functionality, as exemplified in Figure 3a showing that two out of seven WT samples showed small percentages of cell death following irradiation, comparable with the percentage of cell death seen in dysfunctional patients. Finally, promising results were shown for the detection of ATM defects by measuring the percentage of mitotic cells with p53 localization at the centrosome.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 26 An alternative assay, based on measuring CDKN1A levels by RT-PCR following fludarabine and doxorubicin treatment, was primarily designed for ATM function testing and can also distinguish between TP53 and ATM defects. 11 As we have previously published, also cell death following DNA-damaging agents can distinguish a group of functional WT samples from a group of ATM -mutated and a group of TP53 -mutated samples; 22 however, this method seems less suitable to functionally test samples at the individual level to predict (dys)functionality, as exemplified in Figure 3a showing that two out of seven WT samples showed small percentages of cell death following irradiation, comparable with the percentage of cell death seen in dysfunctional patients. Finally, promising results were shown for the detection of ATM defects by measuring the percentage of mitotic cells with p53 localization at the centrosome.…”
Section: Discussionmentioning
confidence: 92%
“…This is corroborated by the fact that apoptotic responses to various DNA-damaging agents were affected in the four cases that were further evaluated. Mutational analysis to uncover an underlying mechanism that could be involved in the observed defective DNA-damage-induced responses showed that two cases carried an SF3B1 mutation, 22 whereas the underlying defects in the other two samples remains elusive. These cases underscore the clinically highly relevant divergence between determination of ATM/p53 status by functional testing and by mutational analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by the fact that apoptotic responses to various DNA-damaging agents were affected in the four cases that were further evaluated. Mutational analysis to uncover an underlying mechanism that could be involved in the observed defective DNA-damageinduced responses showed that two cases carried an SF3B1 mutation, 22 whereas the underlying defects in the other two samples remains elusive. These cases underscore the clinically highly relevant divergence between determination of ATM/p53 status by functional testing and by mutational analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in SF3B1 and TP53 were not mutually exclusive (Table 1), as found in some patient cohorts in the literature [31,32]. To understand the sole effect of SF3B1 mutations, we separated sole SF3B1 mutated cases from patients displaying del17p and/or TP53 mutations.…”
Section: Sf3b1 Mutations In Cll Samples Predict Poor Overall Patient ...mentioning
confidence: 97%